Práticas lean construction: investigação do ensino nos cursos de graduação em engenharia civil - Matuszak, Alexandra Ramos (2020)
Lean Thinking is a set of principles and tools that seeks to reduce or eliminate activities that do not add value to the production processes of a physical good or provide aservice and can be widely used in all manufacturing systems. Lean Construction is the version of Lean Thinking for the Civil Construction sector, a segment of significant socioeconomic impact, and increasingly seeks qualified professionals to optimize production and increase its quality. The market considers differential professionals who have in their curriculum knowledge about Lean Construction to supply this demand. Thus, this dissertation aimed to investigate the insertion and the methodologies used inthe teaching of Lean Construction practices in undergraduate courses in Civil Engineering at a public educational institution in Paraná. The methodology used consisted of the following steps: a literature review to identify the primary practices of Lean Construction and to support the development of the research instruments; a semi-structured interview for the course coordinators and a research instrument for the professors with fifteen questions, structured in three sessions: knowledge about Lean Construction; methods, tools, and techniques used in Lean Construction; teaching/learning methodologies. The teachers' instrument was previously validated by experts with experience in teaching Civil Engineering and Lean Construction. The research was conducted ina Higher Education institution that offers the Civil Engineering course on six campuses. The main results obtained are that there are Lean Construction contents in all campuses, especially in the disciplines of Construction Management and Quality in CivilConstruction. Among the Lean practices listed, the respondents most taught were 5s Methodology, Kanban System, and Layout. From the Lean Construction perspective, teachers practice and teach the most is BIM -Building Information Model. Regarding the teaching methodologies used to teach the contents of Lean Construction, it was observed that 62.5% of teachers teach with conventional methodologies, such as blackboard, multimedia projector, and classroom activities; 56.3% use active methodologies such as PBL(Problem Based Learning) and flipped classroom, 43.8% indicate the realization of applied projects to work the contents of Lean Construction, 31.3% perform practical work in partnership with constructioncompanies, 25% use simulation games.